A Comparative Study on Nitrogen and Phosphorus Concentration Characteristics of Twelve Riparian Zone Species from Upstream of Hunhe River. Issue 4 (30th August 2013) - Yu, Shuai; Chen, Wei; He, Xingyuan; Liu, Zhouli; Song, Hong; Ye, Yin; Huang, Yanqing; Jia, Lian
<x xml:space="preserve">Abstract</x> On upstream of Hunhe River, the riparian zone and water quality has been impacted by increasing anthropogenic activities. Nitrogen and phosphorus run‐off the river, has led to eutrophication. In this study, total nitrogen (TN) and total phosphorus (TP) concentrations were measured from different tissues (roots, stems and leaves) of twelve plants from the upstream riparian zone of the Hunhe River. The TN concentration ranged between 6.45 and 39.94 mg/g, while the TP range was 2.77–9.20 mg/g. A positive correlation of r2 = 0.5157, p < 0.05 was recorded between N/P ratios and TN. This showed that plants growth was limited by N according to the "law of the minimum". The concentrations of TN and TP in leaves were significantly higher than that in roots and stems. There were significant differences among life forms (tree, shrub, and herb) with respect to TP and N/P ratios. The data provided a theoretical guidance to plant species screening for the riparian zone restoration in purpose of the water quality improvement in the Hunhe River.